Identifikasi dan Kesesuaian Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) di Perusahaan Pertambangan Nikel - Hasan, La Ode Abdul; Rosdiana, Rosdiana; Adami, Aryani (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
The development of industrial areas in Bahodopi District, Morowali Regency, has increased the potential for hazardous and toxic waste (B3) from the steel manufacturing industry. This study aims to identify the types and sources of B3 waste and analyze the compliance of its management system at PT. XYZ with Government Regulation Number 22 of 2021. The method used is quantitative descriptive research with a survey approach through observation, questionnaires, and documentation. The analysis then compares the actual conditions of B3 waste management, including sorting, storage, labeling, collection, and transportation, with applicable regulations. The results of the study indicate that PT. XYZ produces B3 waste from its production processes and operational activities, and its management is generally in accordance with regulations. However, improvements are still needed in terms of labeling, storage, and worker understanding to support more optimal and sustainable management.